2020
DOI: 10.3390/s20205786
|View full text |Cite
|
Sign up to set email alerts
|

Effective Melanoma Recognition Using Deep Convolutional Neural Network with Covariance Discriminant Loss

Abstract: Melanoma recognition is challenging due to data imbalance and high intra-class variations and large inter-class similarity. Aiming at the issues, we propose a melanoma recognition method using deep convolutional neural network with covariance discriminant loss in dermoscopy images. Deep convolutional neural network is trained under the joint supervision of cross entropy loss and covariance discriminant loss, rectifying the model outputs and the extracted features simultaneously. Specifically, we design an embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In addition to the findings related to KAP, it is worth noting that recent advancements in image-based techniques, particularly the contributions of artificial intelligence (AI) and machine learning, have shown promising results in the early detection and diagnosis of melanoma. Studies have demonstrated the potential of deep learning algorithms for automated melanoma detection [ 43 , 44 ], as well as the application of multiple instance learning approaches to improve the classification of dysplastic nevi [ 45 , 46 ]. These technological advancements could potentially enhance skin cancer prevention and early intervention efforts by supporting clinicians and empowering patients to identify concerning lesions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the findings related to KAP, it is worth noting that recent advancements in image-based techniques, particularly the contributions of artificial intelligence (AI) and machine learning, have shown promising results in the early detection and diagnosis of melanoma. Studies have demonstrated the potential of deep learning algorithms for automated melanoma detection [ 43 , 44 ], as well as the application of multiple instance learning approaches to improve the classification of dysplastic nevi [ 45 , 46 ]. These technological advancements could potentially enhance skin cancer prevention and early intervention efforts by supporting clinicians and empowering patients to identify concerning lesions.…”
Section: Resultsmentioning
confidence: 99%
“…This model achieved an area under the curve of 90.3%, sensitivity of 86.5%, and specificity of 73.6% compared to the intuitive diagnoses of dermatologists (sensitivity of 77% and specificity of 61.4%), and it can provide valuable assistance to dermatologists in making informed medical decisions that can help to reduce the number of unnecessary excisions. Guo et al proposed a deep convolutional neural network trained with both cross-entropy and covariance discriminant loss [37]. This approach improves the model outputs and extracted features simultaneously, and a new embedding loss is designed to separate the features of melanoma and nonmelanoma images more effectively.…”
Section: Artificial Intelligence-based Approaches Applied To Dermosco...mentioning
confidence: 99%